Ảnh hưởng của các chiến thuật marketing quan hệ tới mong đợi quyền được phục vụ đặc biệt của khách hàng - Trần Thị Bích, Hạnh; Vũ Anh, Dũng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study aims to evaluate the effects of business relationship marketing tactics including using emails/messages, tangible rewards, interpersonal communication, and preferential treatment on customer entitlement. Data were collected through a questionnaire on 283 customers of 12 cosmetics stores and spas in Hanoi. The results indicate that emailing/messaging does not have a significant impact on customer entitlement. However, tangible rewards, interpersonal communication, and preferential treatment significantly have an influence on customer entitlement. In summary, this study concludes with valuable implications for managing customer relations for enterprises and recommendations of potential directions for future research,